Pembagian Harta Bersama Akibat Perceraian di Pengadilan Agama Kediri - Nikmatun Nuzula (MAHAKIM Journal of Islamic Family Law, 2017)
In a general way, the division of community property in divorce at Religion Justice of Kediri utilizes the aught rule on Section 97 Islamic Law Compilations, where is division in that section names that widow or divorce widower lives each get half of community properties. But then available a case where Judges in the Religion Justice of Kedir establish another, which deviates from aught rule in Section 97 Islamic Law Compilation which is, each one third part for husband, and two third part for wife of the community property. This research focuses on 1) What do become the judge’s judgment in deciding matter Number 0168 / Pdt. G / 2014 / PA. Kdr in contrast to aught order in Section 97 KHI; 2) What implications of be applied contra legem in that verdict. In this research, the writer utilizes qualitative approach and field research. Meanwhile, in data collection utilizes interview and documentation. Data analysis uses content analysis of verdict through theory which is available with its practice at the site. This observational result concludes that there is three prime factors of the judge’s judgment in deciding the division matter of the community property Number 0168 / Pdt. G / 2014 / PA. Kdr variably diffrent of section 97 Islamic Law Compilations, which is: 1 ) Since wife while parted by divorces by husband not charge iddah’s earningses, mut ’ ah and past earnings; 2 ) Since wife have greater contributions in render community property; 3 ) as patriarch that ought to meet the family needs, husband has pointed out accountability heaving full as head of family. So if Judge applies rule of law ground, which is by applying Section 97 Islamic Law Compilation are assessed wrongful. Judge moring to advance to perceive justice than rule of law. Therefore of that, Judges in deciding a matter don’t be glued on written order only. Contra legem is form Judge as enforcer of law and justice that not only advance rule of law ground but also utilize justice ground judgment and benefit. Contra legem’s implemented implication can evoke new law that its following can be made as jurisprudence if there is a similar case.